EXIT SUHARTO: OBITUARY FOR A MEDIOCRE TYRANT - Benedict Anderson (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2018)
Suharto is known as the "smiling general", but he also had a complex character which, for most of his life, successfully deflected analysis. He was acclaimed as a man of modest origins who had taken power out of disgust at the corruption of the last years of Sukarno, Indonesia's first president, who ruled from its independence from the Netherlands in 1949 until 1967. But while Suharto become a presiden for years, he presided over a regime in which his closest friends controlled huge monopolies and lucrative concessions, while his children acquired assets worth billions of dollars. Under his rule, Indonesia became closely aligned with western interests during the cold war and was rewarded with aid and investment to foster rapid economic growth, making fortunes for his cronies.